Dual‐Phase Separation in a Semiconfined System: Monodispersed Heterogeneous Block‐Copolymer Membranes for Cell Encoding and Patterning. Issue 19 (15th March 2017) - Wang, Xiuyu; Feng, Xueyan; Ma, Guiping; Zhang, Di; Chai, Yahong; Ge, Maofa; Yao, Li
Abstract : Block copolymers (BCPs) have the capacity to self‐assemble into a myriad of well‐defined aggregate structures, offering great promise for the construction of drug delivery, photolithographic templates, and complex nanoscale assemblies. A uniqueness of these materials is their propensity to become kinetically frozen in non‐equilibrium states, implying that the process of self‐assembly can be utilized to remodel the resulting structures. Here, a new semiconfined system for processing the BCP self‐assembly is constructed, in which an unusual dual‐phase separation occurs, including nonsolvent‐induced microphase separation and osmotically driven macrophase separation, ultimately yielding heterogeneous BCP membranes. These membranes with cellular dimensions show unique anisotropy that can be used for cell encoding and patterning, which are highly relevant to biology and medicine. This processing method not only provides new levels of tailorability to the structures and encapsulated contents of BCP assemblies, but can also be generalized to other block polymers, particularly those with attractive electronic and/or optical properties. Abstract : Dual‐phase separation, including nonsolvent‐induced microphase separation and osmotically driven macrophase separation, is observed in a semiconfined system for processing the self‐assembly of block copolymers, ultimately yielding heterogeneous membranes. These membranes with cellular dimensions show unique anisotropy, which holds great promise for practical applications in cell encoding and patterning.